Distribusi Listrik Menurut Provinsi di Pulau Jawa Tahun 2022 Menggunakan Analisis Korespondensi - Haque, Amara Luzumi Sabila; Wulandari, Sri Pingit (Lembaga Yasin AlSys, 2025)
Electricity distribution in Indonesia is uneven, influenced by economic activity and population density in different regions. This inequality impacts on the quality of life of people in underdeveloped areas and hinders local economic development and the provision of public services. This study aims to analyze the relationship between provinces in Java Island and electricity distribution customer groups using correspondence analysis method. This method explores categorical data without prior assumptions, using contingency tables and biplot visualization to identify relative relationships between groups of variables. The data used includes electricity distribution by province in Java Island in 2022 with customer groups such as commercial, street lighting, government buildings, and industry.The results show the dominance of the customer sector by region, DKI Jakarta is dominant in the commercial group, West Java in street lighting, Central Java in government buildings, DI Yogyakarta and East Java in social, and Banten in industry. In addition, there is a significant relationship between provinces and electricity customer groups that fulfill the dependent assumptions. This study provides an overview of the characteristics of electricity distribution in Java and is expected to help relevant agencies in optimizing resource allocation and planning for more efficient and effective energy infrastructure in the future.